EMPLOYEES' LEGAL STATUS APPOINTED AS DIRECTORS THROUGH RUPS - Yati Nurhayati (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Supreme Court Circular No. 1/2022 stipulates that employees or laborers are appointed directors in the same company through a General Meeting of Shareholders (RUPS) where the employment relationship with the company ends upon appointment as a director. This research aims to ascertain how the severance compensation components and their calculation are entitled to be received by employees appointed as directors through RUPS. This study employs the IRAC writing model, a legal writing technique with the structure of Issue, Rule, Application, and Conclusion. The research findings reveal that Government Regulation No. 35/2021 does not include provisions regarding severance compensation due to the reason of being appointed as a director, leading to a legal vacuum. It creates two possibilities in practice. On the one hand, in cases where an employee resigns from their position to subsequently be appointed as a director, the calculation of compensation for the resignation is applied. On the other hand, companies can establish an internal policy governing severance and compensation calculation mechanisms for employees appointed as directors following best practices. The compensation calculation should consider that it is more than x0.5 because there is no loss or breach, but not exceeding x1.75. After all, the employee does not retire, and the termination of the employment relationship does not result in a complete separation, as the employee continues to work and receives income and benefits from the same company.